THE ROLE OF MULTISPIRAL COMPUTED TOMOGRAPHY IN CLINICAL DIAGNOSIS AND ITS DIAGNOSTIC ADVANTAGES COMPARED WITH MAGNETIC RESONANCE IMAGING - Marozikov N.K.,; Xodjibekova Y.M., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Resume: This article examines the role of multispiral computed tomography (MSCT) in clinical diagnostics and its diagnostic advantages compared with magnetic resonance imaging (MRI). The technical capabilities of modern 128- and 256-slice tomographic systems, including their high spatial resolution, rapid scanning capability, and wide anatomical coverage, are analyzed. The study also reviews the results of scientific research regarding the diagnostic sensitivity, specificity, and overall accuracy of MSCT and MRI technologies. The findings demonstrate that MSCT is highly effective in detecting bone structures, vascular pathologies, traumatic injuries, and emergency conditions. The high speed of examination and superior spatial resolution make this technique particularly valuable in emergency medicine. In conclusion, modern 128- and 256-slice MSCT systems are widely used as effective diagnostic tools for the detection of cardiovascular diseases, oncological pathologies, neurological disorders, and traumatic injuries.